Sikap Petani Terhadap Keberadaan Irigasi dalam Peningkatan Produktivitas Padi Sawah di Desa Tualene Kecamatan Biboki Utara Kabupaten Timor Tengah Utara - Yohanes Lapy Taman; Umbu Joka (Fakultas Pertanian, Universitas Timor, 2019)
This study aims to determine the attitudes of farmers towards the existence of irrigation in increasing the productivity of lowland rice in Tualene Village, North Biboki District, North Central Timor Regency. The method of collecting data sampling is done from the whole object under study and is considered to represent the entire population data collection methods using primary data and secondary data. Data analysis methods in the study include qualitative analysis, Likert scale. The results of the study concluded that 1.) The attitude of farmers to the existence of irrigation in the village of Tualene with a number of respondents 35 people with a percentage of 70 percent expressed strongly agree with the existence of irrigation because irrigation can help expedite, speed up the irrigation process. The existence of irrigation is very helpful in increasing productivity 2.) In conducting paddy farming the farmers have problems in the process of water distribution in irrigation so that it is sought for farmers to work together in water use so as to increase the productivity of wetland rice farming.